1980
DOI: 10.1113/jphysiol.1980.sp013398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucagon on digestive enzyme synthesis, transport and secretion in mouse pancreatic acinar cells.

Abstract: SUMMARY1. Effect of glucagon on amylase secretion and lactic dehydrogenase (LDH) release from functionally intact dissociated pancreatic acinar cells and acini was studied.2. In dissociated rat pancreatic acinar cells, the rate of amylase secretion was increased by 70 % with bethanechol (maximally effective concentration, 10-4 M) and 125 % with A23187 (10-5 M), but the response to cholecystokinin-pancreozymin (CCK-PZ) was inconsistent. In dissociated cells from mouse pancreas, the increases amounted to 78 % wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…TOKUTAKE et al (1976) suggested that inhibition of amino acids on pancreatic exocrine secretion in dogs may be attributed to the direct action of plasma glucagon increased by amino acids administration. The administration of glucagon in vivo causes a short-term inhibition of pancreatic secretion, and in vitro can act directly on the secretion (NAKAJIMA and MAGEE, 1970;MANABE and STEER, 1979;SINGH, 1980). In the present experiment, the inhibitory response induced by amino acids could not be repeated by using exogenous glucagon and insulin.…”
Section: Discussionmentioning
confidence: 60%
“…TOKUTAKE et al (1976) suggested that inhibition of amino acids on pancreatic exocrine secretion in dogs may be attributed to the direct action of plasma glucagon increased by amino acids administration. The administration of glucagon in vivo causes a short-term inhibition of pancreatic secretion, and in vitro can act directly on the secretion (NAKAJIMA and MAGEE, 1970;MANABE and STEER, 1979;SINGH, 1980). In the present experiment, the inhibitory response induced by amino acids could not be repeated by using exogenous glucagon and insulin.…”
Section: Discussionmentioning
confidence: 60%
“…Glucagon's effect on exocrine secretion is inconsistent. Early work using extracted glucagon applied to mouse, guinea pig, or rat pancreatic acinar cells reported a stimulatory influence (115,149,178,179). However, subsequent studies using biologically active synthetic glucagon failed to confirm this finding (149).…”
Section: Pancreatic Hormones and Neuropeptidesmentioning
confidence: 80%
“…Due to theoretical advantages in studying physiological phenomena in single cells (especially the ability to control the extracellular environment rapidly and predictably and a very small extracellular space so that small fluxes of ions critical for secretion can be detected), investigators have tried to use dissociated pancreatic acinar cells obtained by combined procedures of digestion of tissue by enzymes, mechanical disruption and Ca2+ chelation with EGTA or EDTA (Amsterdam & Jamieson, 1974a;Gardner, Conlon, Klaeveman, Adams & Ondetti, 1975;Williams, Cary & Moffat, 1976;Kondo & Schulz, 1976;Kempen, DePont & Bonting, 1977;Renckens, Schrijen, Swarts, DePont & Bonting, 1978;Case & Clausen (see Case, 1978); Singh, 1978Singh, , 1980b. However, in practice, it has been observed that dissociated cells respond poorly to physiological secretagogues (Kondo & Schulz, 1976), possibly due to damage of cell surface receptors (Case, 1978) and need about a tenfold greater concentration of agonists than intact tissue to elicit enzyme secretion (Amsterdam & Jamieson, 1974b;Williams et at.…”
Section: Discussionmentioning
confidence: 99%
“…Cell counts showed that more than 95 % of the cells were acinar and were intact by trypan Blue exclusion studies. Characterization of isolated cells, including intracellular ion content and response to secretagogues, is reported elsewhere (Singh, 1980b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation